ANTESEDEN PERCEIVED ENJOYMENT DAN IMPLIKASINYA TERHADAP KONTINUITAS PENGGUNAAN MOBILE GAME - Kurnia; Natalia Sukarnadi (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The transition of digital media and platforms has driven new markets for the mobile game industry. Currently, the video game segment has been adapting platforms and driving a significant increase in users and driving intense market competition. In an increasingly competitive climate, marketing success does not only depend on increasing the number of downloads but also on continued use based on the ability to meet user expectations, in the context of using mobile games users have a variety of pleasures to be fulfilled. This study identified the influencing factors (antecedents) of perceived enjoyment and their implications for the continuity of mobile game use. The results of this study indicate that Design Aesthetic, Perceived Ease of Use, Challenge, Variety, Novelty, and Interactivity can significantly become antecedents that determine the fulfillment of perceived enjoyment by mobile game users. The results of this study also have implications for the literature regarding the evaluation of sustainable relationship values, where Perceived Enjoyment was found to be significant in determining the continuity of mobile game use as a consequence of the relationship between antecedents as a predictor. Keywords: Perceived Enjoyment, Continuous Intention, Mobile Game